Method for producing adsorption filter
By fixing small adsorbent particles onto larger ones within a specific ratio, the method addresses high pressure loss and inconsistent performance in existing filters, achieving high pollutant removal rates with low pressure loss.
Patent Information
- Application Number
- JP2023107691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Existing filters for removing volatile organic compounds suffer from high pressure loss due to particle aggregation and irregular structures, leading to inconsistent performance.
A method involving the use of adsorbent A with a large particle length (200 μm to 1000 μm) and adsorbent B with a small particle length (0.1 μm to 100 μm), fixed at a ratio of 0.3 to 150, to increase surface area and create voids, preventing clogging and reducing pressure loss.
The method enhances pollutant removal rates while maintaining low pressure loss, improving adsorption performance and contributing to energy savings.
Smart Images

Figure 2025006716000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing an adsorptive filter for removing contaminants. [Background technology]
[0002] In recent years, as one of the measures to deal with environmental problems, interest in measures against odor pollution has been growing. For example, odor pollution is pollution caused by exhaust gas. Among exhaust gases, volatile organic compounds such as toluene and acetaldehyde are considered to be causative substances of sick house syndrome, and the removal and deodorization of these odorous substances is a major issue. It is known that these exhaust gases can be removed by filters attached to air purification devices such as air purifiers and air conditioners. It is preferable that this filter has low pressure loss, i.e., high breathability.
[0003] There is a high demand for filters that have high pollutant removal performance and low pressure loss to remove the above-mentioned pollutants. In response to this demand, for example, in Patent Document 1, activated carbon particles of the same particle diameter are bonded and aggregated with a thermoplastic resin to form irregular aggregates, thereby creating voids between the aggregates, thereby realizing low pressure loss. In addition, in Patent Document 2, particles with an average particle diameter of 1 μm or less are supported on a nonwoven fabric, thereby achieving high volatile organic compound removal performance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 3612329 [Patent Document 2] JP 2015-157250 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the filter of Patent Document 1 has problems such as the aggregates collapsing due to the external force applied when forming the adsorbent into a sheet, filling the voids and increasing the pressure loss, and the irregular structure of the molded aggregates results in a large variation in performance. Also, the filter of Patent Document 2 has problems such as the particle diameter of the particles used being small, and the adsorbent particles filling the voids between the nonwoven fibers and increasing the pressure loss.
[0006] In view of the above circumstances, an object of the present invention is to provide a method for manufacturing an adsorption filter that has high performance for removing pollutants including volatile organic compounds and has low pressure loss. [Means for solving the problem]
[0007] The method for manufacturing an adsorption filter according to an embodiment of the present invention that solves the above problems is as follows. [1] The method includes the steps of preparing an adsorbent A having an average particle length of 200 μm to 1000 μm, an adsorbent B having an average particle length of 0.1 μm to 100 μm, and a substrate, adsorbing the adsorbent B onto the surface of the adsorbent A to obtain an adsorbent, and supporting the adsorbent on the substrate, and the weight W of the adsorbent A is calculated. A and the weight W of the adsorbent B B Ratio of W A / W B The value P is 0.3 or more and 150 or less, and when the total amount of adsorbent B is 100%, 65% or more of adsorbent B is fixed to the surface of adsorbent A.
[0008] According to the above-mentioned method for producing an adsorption filter, by using an adsorbent B having a small average particle major axis of 0.1 μm to 100 μm, the surface area for adsorbing contaminants can be increased, and the removal rate of contaminants can be increased. In addition, the adsorbent B having a small average particle major axis is fixed to the surface of the adsorbent A having a large average particle major axis of 200 μm to 1000 μm, and the weight W A and the weight W of the adsorbent B B Ratio of W A / W BBy setting the value P to be 0.3 or more and 150 or less, it becomes easy to create gaps between the adsorbent particles. In addition, since 65% or more of the total number of adsorbents B (100%) is fixed to the surface of adsorbent A, there is little adsorbent B remaining free from the surface of adsorbent A, and it is possible to prevent adsorbent B from filling the gaps in the substrate and causing clogging. This makes it possible to manufacture an adsorption filter with low pressure loss.
[0009] The method for producing an adsorption filter according to an embodiment of the present invention is preferably any one of the following methods [2] to [8]. [2] Average particle length R of the adsorbent A A and the average particle length R of the adsorbent B B Ratio of R B / R A The method for producing an adsorption filter according to [1], wherein the ratio of the adsorption rate to the total adsorption rate is 1 / 5000 to 1 / 5. [3] Average particle length R of the adsorbent A A , the average particle major axis R of the adsorbent B B , and the weight ratio P of the adsorbent A to the adsorbent B ((the weight W of the adsorbent A) A ) / (Weight of adsorbent B W B )) is P=R A 3 / [{(R A +2R B ) 3 -R A 3}×X], where X is 0.1 or more and 10 or less. [4] The method for manufacturing an adsorption filter according to any one of [1] to [3], wherein the step of fixing the adsorbent B to the surface of the adsorbent A to obtain an adsorbent includes a step of mixing the adsorbent A, the adsorbent B and a binder. [5] The method for manufacturing an adsorption filter described in [4], wherein the binder is at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof. [6] The method for producing an adsorption filter according to any one of [1] to [5], wherein the adsorbent A is any one of activated carbon, activated alumina, silica gel, and zeolite. [7] The method for producing an adsorption filter according to any one of [1] to [6], wherein the adsorbent B is any one of activated carbon, activated alumina, silica gel, and zeolite. [8] The method for producing an adsorption filter according to any one of [1] to [7], wherein the base material is a nonwoven fabric. Effect of the Invention
[0010] According to the above-described method for manufacturing an adsorption filter, it is possible to manufacture an adsorption filter that has an improved pollutant removal performance, by increasing the removal rate of pollutants such as volatile organic compounds and reducing pressure loss. [Brief description of the drawings]
[0011] [Figure 1] 1 is a scanning electron microscope photograph of the adsorbent obtained in Example 2. [Diagram 2] 1 is a scanning electron microscope photograph of the adsorption filter obtained in Example 2 after the substrate was peeled off. [Diagram 3] 1 is a scanning electron microscope photograph of the adsorption filter obtained in Comparative Example 4 after the substrate was peeled off. [Figure 4] 1 is a graph showing the relationship between the toluene removal rate and the pressure loss of the adsorption filters of Examples 1 to 16 and Comparative Examples 1 to 6. [Diagram 5] 1 is a graph showing the relationship between the toluene removal rate and the pressure loss of the adsorption filters of Example 17 and Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the present invention will be described based on the embodiments. However, the present invention is not limited to the following embodiments, and it is possible to carry out the present invention by making appropriate modifications within the scope of the above and below described spirit, and all of these modifications are included in the technical scope of the present invention.
[0013] A method for manufacturing an adsorption filter according to an embodiment of the present invention includes the steps of preparing an adsorbent A having an average particle length of 200 μm to 1000 μm, an adsorbent B having an average particle length of 0.1 μm to 100 μm, and a substrate; adsorbent B is fixed to the surface of adsorbent A to obtain an adsorbent; and adsorbent consisting of adsorbent A and adsorbent B is supported on the substrate.
[0014] Since adsorption occurs at the interface between the gas phase, liquid phase, or solid phase and the adsorbent, by increasing the contact probability at the interface between the adsorbent and the adsorbed substance, the adsorbed substance can be adsorbed by the adsorbent with high efficiency. In the manufacturing method of the adsorption filter according to the embodiment of the present invention, by using the adsorbent B having a small average particle major axis of 0.1 μm to 100 μm, the surface area per unit volume of the adsorbent in the manufactured adsorption filter is increased, and an adsorption filter with a high removal rate of pollutants can be manufactured. In addition, if the particle size of the adsorbent particles is small, the voids are filled and the packing density becomes high, which results in high pressure loss. In this regard, the manufacturing method of the adsorption filter according to the embodiment of the present invention includes a step of fixing the adsorbent B having a small average particle major axis to the surface of the adsorbent A having a large average particle major axis of 200 μm to 1000 μm to obtain an adsorbent, and the weight W of the adsorbent A is increased. A and the weight W of the adsorbent B B Ratio of W A / W B Adsorbent A and adsorbent B are used so that the value P of is 0.3 to 150. As a result, gaps are easily formed between the adsorbent particles in the adsorption filter, so that the packing density is not too high. Furthermore, since 65% or more of the total number of adsorbents B (100%) is fixed to the surface of adsorbent A, there is little adsorbent B that is free from the surface of adsorbent A, and it is possible to prevent adsorbent B from filling the gaps in the substrate and causing clogging. As a result, an adsorption filter with low pressure loss can be obtained. When the adsorption filter manufactured by the manufacturing method according to the embodiment of the present invention is attached to an air purification device such as an air purifier or an air conditioner and used, the differential pressure between the upstream side and downstream side of the adsorption filter is small, improving the adsorption performance and contributing to energy saving.
[0015] Adsorbent A having an average particle major axis of 200 μm to 1000 μm and adsorbent B having an average particle major axis of 0.1 μm to 100 μm can be obtained by sieving the adsorbent particles through a mesh. The mesh size can be selected according to the major axis of the particles to be obtained, for example, adsorbent A having a large average particle major axis is obtained by excluding particles that can pass through a mesh of No. 18 but cannot pass through a mesh of No. 65 or more, and adsorbent B having a small average particle major axis is obtained by sieving through a mesh of No. 160 or more.
[0016] The average particle major axis of the adsorbent A is 200 μm or more, preferably 250 μm or more, more preferably 300 μm or more, even more preferably 350 μm or more, particularly preferably 375 μm or more, and may be 400 μm or more. If the lower limit of the average particle major axis of the adsorbent A is within the above range, the pressure loss of the adsorption filter can be reduced. In addition, the average particle major axis of the adsorbent A is 1000 μm or less, preferably 900 μm or less, more preferably 850 μm or less, even more preferably 800 μm or less, and may be 750 μm or less. If the upper limit of the average particle major axis of the adsorbent A is within the above range, there is an advantage that the thickness of the adsorption filter does not become too thick and manufacturing is easy.
[0017] The average particle major axis of the adsorbent B is 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 5 μm or more. If the lower limit of the average particle major axis of the adsorbent B is within the above range, the cohesive force of the adsorbent B is not too strong, and the adsorbent B can be uniformly fixed to the surface of the adsorbent A. In addition, the average particle major axis of the adsorbent B is 100 μm or less, preferably 75 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. If the upper limit of the average particle major axis of the adsorbent B is within the above range, the adsorption force of the adsorbent B to the surface of the adsorbent A can be secured, and it is easy to prevent the adsorbent B from falling off from the adsorbent A. By having the average particle major axis of the adsorbent B within the above range, it is possible to uniformly and strongly adhere the adsorbent B to the surface of the adsorbent A.
[0018] The method for fixing adsorbent B to the surface of adsorbent A is not particularly limited, but examples thereof include a method in which adsorbent A and adsorbent B are immersed in an aqueous solution in which a water-soluble polymer is dissolved, stirred, and then dried, and a method in which an aqueous solution in which a water-soluble polymer is dissolved is made into a mist or mist form and sprayed onto adsorbent A and adsorbent B, and then dried.
[0019] The step of adhering adsorbent B to the surface of adsorbent A preferably includes a step of mixing adsorbent A, adsorbent B, and a binder. By mixing adsorbent A, adsorbent B, and a binder, it becomes easier to adhere adsorbent B to the surface of adsorbent A.
[0020] The binder is not particularly limited as long as it can fix the adsorbent B to the surface of the adsorbent A, and examples thereof include water-soluble polymers, thermoplastic resins, and water-dispersible polymers. In particular, the binder is preferably a water-soluble polymer. The water-soluble polymer preferably has a solubility in water of 1 g or more at 20° C. and 1 atm, and a molecular weight of 10,000 or more. The binder is preferably a water-soluble polymer, and is preferably at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof.
[0021] By using a water-soluble polymer as the binder, adsorbent B can be easily fixed to the surface of adsorbent A even if only a small amount of binder is added.
[0022] The binder solution concentration is preferably 0.1% by weight to 10% by weight, and more preferably 1% by weight to 5% by weight. By setting the binder solution concentration to 0.1% by weight or more, the adhesive force of adsorbent B to the surface of adsorbent A can be ensured. By setting the binder solution concentration to 10% by weight or less, the problem of the binder coating the adsorbent particles, which occurs when the binder solution concentration exceeds 10% by weight, can be avoided. The binder solution concentration may be the solution concentration of the water-soluble polymer.
[0023] The method of supporting the adsorbent consisting of adsorbent A and adsorbent B on the substrate is not particularly limited, and any known processing method can be used. For example, (a) a wet sheeting method in which adsorbent A and adsorbent B are dispersed in water together with the fibers constituting the substrate and dehydrated, (b) an airlaid method in which adsorbent A and adsorbent B are dispersed in air together with the fibers constituting the substrate, (c) a method in which adsorbent A and adsorbent B are filled between two or more layers of nonwoven fabric, woven fabric, net-like material, film, membrane, etc. by thermal adhesion, (d) a method in which adsorbent A and adsorbent B are bonded and supported on breathable materials such as nonwoven fabric, woven fabric, and urethane foam using an emulsion adhesive or a solvent-based adhesive, (e) a method in which adsorbent A and adsorbent B are bonded and supported on breathable materials such as nonwoven fabric, woven fabric, and urethane foam using the thermoplasticity of a thermoplastic resin, and (f) a method in which adsorbent A and adsorbent B are mixed and integrated by kneading them into fibers or resin, etc., can be used according to the application. In particular, among the above processing methods, it is preferable to use processing methods (b), (c), and (e) since it is not necessary to use a surfactant and the adsorbent can be prevented from being covered with the surfactant.
[0024] The step of supporting the adsorbent consisting of adsorbent A and adsorbent B on the substrate is preferably performed after the step of obtaining an adsorbent by fixing adsorbent B to the surface of adsorbent A. That is, it is preferable to support adsorbent A with adsorbent B fixed to the surface on the substrate, and in the above methods (a) to (f), "adsorbent A and adsorbent B" can be read as "adsorbent A with adsorbent B fixed to the surface". This allows adsorbent B to be easily fixed to the surface of adsorbent A. This allows the step of easily fixing adsorbent B to the surface of adsorbent A to be easily performed. Alternatively, the step of fixing adsorbent B to the surface of adsorbent A to obtain an adsorbent and the step of supporting the adsorbent on the substrate may be performed simultaneously. In this case, the "step of supporting the adsorbent on the substrate" can be understood as the "step of supporting adsorbent A and adsorbent B on the substrate".
[0025] The substrate is preferably molded into a planar, pleated, or honeycomb shape. The pleated shape, when used as a cross-flow filter, and the honeycomb shape, when used as a flat-flow filter, can increase the contact area with the gas to be treated, improving the removal rate of pollutants and simultaneously reducing the pressure loss of the filter.
[0026] The substrate is preferably a nonwoven fabric. The type of nonwoven fabric is not particularly limited, but is preferably a needle-punched nonwoven fabric that can be formed by piercing needles with protrusions to entangle fibers, a spunlace nonwoven fabric that can be formed by entangling fibers with a high-pressure water flow, a spunbond nonwoven fabric that can be formed by bonding a web formed from long fibers into a sheet, or a laminate thereof. When stacking nonwoven fabrics, it is preferable to bond each layer using, for example, a needle. The substrate may be an electret nonwoven fabric obtained by electrically charging a nonwoven fabric. Needless to say, the substrate may be a material other than a nonwoven fabric, and the substrate of the nonwoven fabric may contain another material such as a knitted fabric or a woven fabric.
[0027] Weight of adsorbent A W A and the weight of adsorbent B W B Ratio of WA / W B The value P is 0.3 or more, and can be 0.5 or more, 1 or more, 2 or more, 3 or more, 5 or more, 7 or more, 10 or more, etc. A / W B The value P is 150 or less, and can be 120 or less, 100 or less, 90 or less, 80 or less, 70 or less, 50 or less, etc. A / W B If the value P is within the above range, the surface area for adsorbing pollutants by adsorbent B can be increased, thereby increasing the pollutant removal rate, while voids can be secured by adsorbent A, thereby keeping the pressure loss of the adsorption filter low.
[0028] When the total number of adsorbents B is 100%, the number of adsorbents B adhering to the surface of adsorbent A is 65% or more. Adsorbents B not adhering to the surface of adsorbent A may fill the voids of the substrate and increase the pressure loss of the adsorption filter. However, since the number of adsorbents B adhering to the surface of adsorbent A is 65% or more out of the total number of adsorbents B (100%), the number of adsorbents B that are not adhering to the surface of adsorbent A and are free to fill the voids of the substrate is reduced, so that the pressure loss of the adsorption filter can be kept low. The proportion of adsorbents B adhering to the surface of adsorbent A is more preferably 70% or more, more preferably 75% or more, even more preferably 80% or more, and particularly preferably 90% or more. If the lower limit of the proportion of adsorbents B adhering to the surface of adsorbent A is within the above range, the pressure loss of the adsorption filter can be reduced. The ratio of adsorbent B adhering to the surface of adsorbent A is ideally 100%, but may realistically be 99% or less, 98% or less, 96% or less, or 95% or less.
[0029] The proportion of adsorbent B adhering to the surface of adsorbent A can be obtained from a micrograph taken with a scanning electron microscope (SEM) or the like. The proportion of adsorbent B adhering to the surface of adsorbent A can be determined, for example, by removing at least a part of the substrate so that adsorbent A and adsorbent B can be observed, observing with an SEM so that at least 10 adsorbents A are included in one field of view, and counting the number of adsorbents B adhering to the surface of adsorbent A and the number of adsorbents B not adhering to the surface of adsorbent A but present in the gaps of adsorbent A in the field of view. The measurement may be performed by actually counting the number of adsorbents B, or by visually determining the number of adsorbents B adhering to the surface of adsorbent A and the number of adsorbents B not adhering to the surface of adsorbent A but present in the gaps of adsorbent A.
[0030] The number of adsorbents B adhering to each particle of adsorbent A is preferably 500 or more, more preferably 600 or more, even more preferably 800 or more, even more preferably 1000 or more, and particularly preferably 2000 or more. If the lower limit of the number of adsorbents B adhering to each particle of adsorbent A is within the above range, the surface area for adsorbing contaminants by adsorbent B can be increased, so that the removal rate of contaminants can be improved. The upper limit of the number of adsorbents B adhering to each particle of adsorbent A is not particularly limited, but may be, for example, preferably 2,000,000 or less, more preferably 1,000,000 or less, more preferably 500,000 or less, particularly preferably 100,000 or less, 80,000 or less, 50,000 or less, 30,000 or less, 10,000 or less, 9,000 or less, or 8,000 or less. The number of particles of adsorbent B that can adhere to the surface of adsorbent A depends on the size of adsorbent B relative to the surface area of adsorbent A. However, if the upper limit of the amount of adsorbent B adhered to each particle of adsorbent A is within the above-mentioned range, adsorbent B is less likely to fall off the surface of adsorbent A, and clogging due to fallen adsorbent can be prevented, thereby reducing the pressure loss of the adsorption filter.
[0031] The number of adsorbents B adhering to each particle of adsorbent A can be obtained from a micrograph taken with a scanning electron microscope (SEM) or the like. The number of adsorbents B adhering to each particle of adsorbent A can be obtained, for example, by removing at least a portion of the substrate so that adsorbents A and B can be observed, observing 10 adsorbent particles with an SEM, counting the number of adsorbents B adhering to the surface of adsorbent A in each case, and assuming that the same number of adsorbents B are adhering to the surface opposite to the observation surface, doubling this number, and averaging the measured values obtained for the 10 particles.
[0032] Average particle length R of adsorbent A A and the average particle length R of the adsorbent B B Ratio of R B / R A The ratio R is preferably 1 / 5000 to 1 / 5, more preferably 1 / 1000 to 1 / 10, further preferably 1 / 500 to 1 / 20, and most preferably 1 / 100 to 1 / 30. B / R A By setting the ratio R to 1 / 5000 or more, the cohesive force of adsorbent B is not too strong, and adsorbent B can be uniformly fixed to the surface of adsorbent A. B / R A When the ratio of the surface area of adsorbent B to the surface area of adsorbent A is 1 / 5 or less, the size of adsorbent B relative to the surface area of adsorbent A does not become too large, making it easier to ensure the adhesion of adsorbent B to the surface of adsorbent A and preventing adsorbent B from falling off from adsorbent A.
[0033] Average particle length R of adsorbent A A , the average particle major axis R of the adsorbent B B and the weight ratio P of the adsorbent A to the adsorbent B ((weight of adsorbent A) / (weight of adsorbent B)) preferably satisfies the relationship of the following formula (1). P=R A 3 / [{(R A +2R B ) 3 -R A 3}×X]...Equation (1)
[0034] Equation (1) indicates that the weight ratio P ((weight of adsorbent A) / (weight of adsorbent B)) corresponds to (volume of adsorbent A) / (volume of adsorbent B). Here, the volume of adsorbent A is approximately R A 3 In addition, in the case of adsorbent C, adsorbent B is fixed to both sides of adsorbent A, and the major axis R of adsorbent A is A The major axis R of adsorbent B is B Add twice the volume of the adsorbent and cube it to get the volume of the adsorbent (R A +2R B ) 3 From this, the volume of adsorbent A is R A 3 By subtracting A +2R B ) 3 -R A 3 The smaller X is, the smaller the amount of adsorbent B adhering to the surface of adsorbent A is, and the larger X is, the larger the amount of adsorbent B adhering to the surface of adsorbent A is.
[0035] X is preferably 0.1 to 10, more preferably 0.2 to 8.0, even more preferably 0.4 to 5.0, and most preferably 0.5 to 2.0. If X is within this range, adsorbent B can be uniformly fixed to the surface of adsorbent A. If X is less than 0.1, the amount of adsorbent B is too small, making it difficult to obtain the effects of the present invention. If X is greater than 10, it is considered that multiple layers of adsorbent B are deposited on the surface of adsorbent A, and even if the amount of adsorbent B is increased so that X is greater than 10, it is unlikely that the effect of reducing the pressure loss of the adsorption filter will be improved compared to when X is 0.1 to 10. Conversely, if X is too large, adsorbent B will be easily detached from the surface of adsorbent A, which is considered to increase the pressure loss of the adsorption filter. From this viewpoint, X is preferably 15 or less, more preferably 12 or less.
[0036] Adsorbent A and adsorbent B are preferably made of a material capable of capturing ions or molecules of contaminants, such as toluene or acetaldehyde, contained in the gas phase, thereby removing them from the gas phase.
[0037] The adsorbent A is not particularly limited as long as it is the above-mentioned material, but is preferably any one of activated carbon, activated alumina, silica gel, and zeolite. These may be used alone or in combination of two or more. To remove volatile organic compounds such as toluene and aldehydes, the adsorbent A is preferably composed of activated carbon or silica gel.
[0038] The adsorbent B is not particularly limited as long as it is the above-mentioned material, but is preferably any one of activated carbon, activated alumina, silica gel, and zeolite. These may be used alone or in combination of two or more. To remove volatile organic compounds such as toluene and aldehydes, the adsorbent B is preferably composed of activated carbon or silica gel.
[0039] The material constituting adsorbent A and the material constituting adsorbent B may be the same or different, but are preferably the same, which can ensure the adhesive force of adsorbent B to the surface of adsorbent A.
[0040] The activated carbon is not particularly limited, but it is preferable to use common activated carbon such as coconut shell activated carbon, coal-based activated carbon, wood-based activated carbon, and synthetic resin-based activated carbon in terms of performance and availability.
[0041] The BET specific surface area of the activated carbon is not particularly limited, but is preferably 800 m 2 / g~1500m 2 / g is preferred, and 850m 2 / g~1300m 2 / g is more preferable. 2 / g or more, it is easy to obtain a deodorizing effect. In addition, the BET specific surface area of the activated carbon is 1500 m 2 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0042] The pore volume of the activated carbon is not particularly limited, but is preferably 0.30 cm 3 / g~0.70cm 3 / g is preferred, and 0.40 cm 3 / g~0.55cm 3 / g is more preferable. 3 / g or more, the deodorizing effect is easily obtained. 3 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0043] The average pore diameter of the activated carbon can be appropriately adjusted depending on the object to be adsorbed. For example, when the object to be adsorbed is toluene, the average pore diameter is preferably 15 Å to 19 Å, and more preferably 16 Å to 18 Å.
[0044] The BET specific surface area of the silica gel is not particularly limited, but is preferably 20 m 2 / g~1000m 2 / g is preferred, 50m 2 / g~700m 2 / g is more preferable. The BET specific surface area of the silica gel is 20 m 2 / g or more, the deodorizing effect is easily obtained. In addition, the BET specific surface area of the silica gel is 1000 m 2 / g or less, it is possible to prevent contaminants that have been adsorbed from being desorbed.
[0045] The adsorption filter manufactured by the manufacturing method according to the embodiment of the present invention can remove ions and molecules contained in the gas phase, such as toluene and acetaldehyde, from the target gas phase by incorporating them therein, and can be used for various purposes. Although not particularly limited, the adsorption filter can be used indoors, in vehicles, etc., and is preferably used in wallpaper, furniture, interior materials, resin molded bodies, electrical equipment, etc. EXAMPLES
[0046] The present invention will be described below with reference to examples. The present invention is not limited to the examples, and any design modifications made in accordance with the spirit described above and below are included within the technical scope of the present invention.
[0047] (Proportion of adsorbent B adhering to adsorbent A) One side of the nonwoven fabric was peeled off from the adsorption filter obtained in each Example and Comparative Example, and the filter was observed with a scanning electron microscope (SEM) so that at least 10 particles of adsorbent A were included in one field of view. Of the total number of adsorbents B captured in the SEM observation photograph (100%), the number of particles of adsorbent B adhering to the surface of adsorbent A and the number of particles of adsorbent B not adhering to the surface of adsorbent A but existing in the gaps between adsorbent A were determined by visual estimation, and the proportion of adsorbent B adhering to adsorbent A was calculated.
[0048] (Toluene removal rate) Cross-sectional area 36cm 2 A sheet-formed adsorbent (adsorption filter) was sandwiched between the columns. Air with a toluene vapor concentration of 80 ppm was supplied to the column at a linear velocity of 20 cm / sec, a temperature of 25°C, and a humidity of 50% RH. The toluene concentration at the column outlet was measured after 1 minute, and the removal rate (η) was calculated using the following formula (2). In the following formula (2), Ci (ppm) is the toluene inlet concentration, and Co (ppm) is the toluene outlet concentration. The toluene concentration was measured using a hydrocarbon system. Removal rate η(%)=[1-(Co / Ci)]×100 ···(2)
[0049] (Pressure loss) A sheet of adsorbent (adsorption filter) was placed inside the duct, and the linear velocity passing through the filter was controlled to be 10.4 cm / sec. The pressure loss (mmaq) was calculated by reading the static pressure difference upstream and downstream of the filter with a pressure gauge.
[0050] <Example 1> Adsorbent A was granular activated carbon (average particle diameter 300 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) in a weight ratio of 3:1, i.e., the weight W A and the weight W of the adsorbent B B Ratio of W A / W B The activated carbon particles were mixed so that the value P of the activated carbon particles was 3, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the granular activated carbon and powdered activated carbon, and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent with powdered activated carbon fixed to the surface of the granular activated carbon.
[0051] The downstream layer is a thermal bond nonwoven fabric, and the above-obtained absorbent is mixed with a thermoplastic powder resin as an adhesive in a weight ratio of 20:1 to form a 200g / m2 2 The adsorption filter was heated using an electret nonwoven fabric as the upstream layer, and an adsorption filter in which the adsorbent was supported on the nonwoven fabric was obtained. For this adsorption filter, the number of adsorbent B adhering to adsorbent A, the ratio of adsorbent B adhering to the surface of adsorbent A, the toluene removal rate, and the pressure loss were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 1.
[0052] <Comparative Example 1> Granular activated carbon (average particle diameter 300 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 The adsorption filter was fabricated by forming a sheet of a thermobond nonwoven fabric as the downstream layer, and the above adsorbent and a thermoplastic powder resin as an adhesive were mixed in a weight ratio of 20:1 to form a sheet with a basis weight of 200 g / m2. 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 1.
[0053] [Table 1]
[0054] In Example 1 and Comparative Example 1, the pressure loss was equivalent because the average particle length of the granular activated carbon (adsorbent A) used was the same. However, since powdered activated carbon (adsorbent B) was not used in Comparative Example 1, the toluene removal rate was lower than that of Example 1.
[0055] <Example 2> Adsorbent A was granular activated carbon (average particle diameter 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) in a weight ratio of 7:1, i.e., the weight W A and the weight W of the adsorbent B B Ratio of W A / W B The activated carbon particles were mixed so that the value P of the activated carbon particles was 7, and then an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the granular activated carbon and powdered activated carbon, and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the granular activated carbon. An SEM photograph of the obtained adsorbent is shown in Figure 1.
[0056] The downstream layer is a thermal bond nonwoven fabric, and the above-mentioned absorbent and thermoplastic powder resin as an adhesive are mixed in a weight ratio of 20:1 to form a 200g / m2 2The adsorption filter was heated using an electret nonwoven fabric as the upstream layer, and an adsorption filter in which the adsorbent was supported on the nonwoven fabric was obtained. For this adsorption filter, the number of adsorbent B adhering to adsorbent A, the ratio of adsorbent B adhering to the surface of adsorbent A, the toluene removal rate, and the pressure loss were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 2. Also, an SEM photograph taken after peeling off the nonwoven fabric on one side is shown in Figure 2.
[0057] <Example 3> The weight ratio of adsorbent A to adsorbent B is 50:1, i.e., the weight of adsorbent A is W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was manufactured in the same manner as in Example 2, except that the value P was changed to 50. The manufacturing conditions and the measurement results are shown in Table 2.
[0058] <Example 4> The weight ratio of adsorbent A to adsorbent B is 1:1, that is, the weight of adsorbent A is W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was manufactured in the same manner as in Example 2, except that the value P was changed to 1. The manufacturing conditions and the measurement results are shown in Table 2.
[0059] <Example 5> The weight ratio of adsorbent A to adsorbent B is 1:2, that is, the weight of adsorbent A is W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was manufactured in the same manner as in Example 2, except that the value P was changed to 0.5. The manufacturing conditions and the measurement results are shown in Table 2.
[0060] <Example 6> Except for changing the concentration of the aqueous sodium alginate (ALG-Na) solution mixed with the granular activated carbon and powdered activated carbon to 9.0% by weight, an adsorptive filter was manufactured in the same manner as in Example 2. The manufacturing conditions and measurement results are shown in Table 2.
[0061] <Example 7> Except for changing the concentration of the aqueous sodium alginate (ALG-Na) solution mixed with the granular activated carbon and powdered activated carbon to 2.0% by weight, an adsorptive filter was manufactured in the same manner as in Example 2. The manufacturing conditions and measurement results are shown in Table 2.
[0062] <Example 8> An adsorption filter was manufactured in the same manner as in Example 2, except that the molecular weight of sodium alginate (ALG-Na) mixed with the granular activated carbon and powdered activated carbon was changed to 80000. The manufacturing conditions and measurement results are shown in Table 2.
[0063] <Example 9> An adsorption filter was manufactured in the same manner as in Example 2, except that the molecular weight of sodium alginate (ALG-Na) mixed with the granular activated carbon and powdered activated carbon was changed to 100,000. The manufacturing conditions and measurement results are shown in Table 2.
[0064] <Example 10> An adsorption filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4% by weight aqueous solution of polyvinyl alcohol (PVA) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of the polyvinyl alcohol (PVA) was 90,000. The manufacturing conditions and measurement results are shown in Table 2.
[0065] <Example 11> An adsorptive filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4 wt% aqueous polyacrylamide (PAM) solution instead of the aqueous sodium alginate (ALG-Na) solution. The manufacturing conditions and measurement results are shown in Table 2.
[0066] <Example 12> An adsorption filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4% by weight aqueous solution of carboxymethylcellulose (CMC) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of the carboxymethylcellulose (CMC) was 120,000. The manufacturing conditions and measurement results are shown in Table 2.
[0067] <Example 13> An adsorption filter was manufactured in the same manner as in Example 2, except that the granular activated carbon and powdered activated carbon were mixed with a 4.4% by weight aqueous solution of polyvinylpyrrolidone (PVP) instead of the aqueous solution of sodium alginate (ALG-Na). The molecular weight of polyvinylpyrrolidone (PVP) was 360,000. The manufacturing conditions and measurement results are shown in Table 2.
[0068] <Example 14> Adsorbent A was granular activated carbon (average particle diameter 900 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) was used, and adsorbent A and adsorbent B were mixed in a weight ratio of 10:1, i.e., the weight of adsorbent A W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was produced in the same manner as in Example 2, except that the mixing was performed so that the value P of was 10. The production conditions and the measurement results are shown in Table 2.
[0069] <Example 15> Adsorbent B was powdered activated carbon (average particle length 50 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) was used, and adsorbent A and adsorbent B were mixed in a weight ratio of 2:1, i.e., the weight of adsorbent A W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was produced in the same manner as in Example 2, except that the mixing was performed so that the value P of was 2. The production conditions and the measurement results are shown in Table 2.
[0070] <Example 16> Adsorbent B was powdered activated carbon (average particle length 1 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) were used, and adsorbent A and adsorbent B were mixed in a weight ratio of 100:1, i.e., the weight of adsorbent A W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was produced in the same manner as in Example 2, except that the mixing was performed so that the value P of was 100. The production conditions and the measurement results are shown in Table 2.
[0071] [Table 2]
[0072] <Comparative Example 2> The downstream layer is made of thermal bond nonwoven fabric, and the downstream layer is made of granular activated carbon (average particle length 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17Å) was mixed with thermoplastic powder resin as adhesive in a weight ratio of 20:1, and the resulting mixture had a basis weight of 200g / m 2 The mixture was sprayed so that the concentration of the activated carbon in the adsorption filter was 100%. An electret nonwoven fabric was used as the upstream layer and heated to obtain an adsorption filter in which granular activated carbon was supported on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 3.
[0073] <Comparative Example 3> Granular activated carbon (average particle diameter 900 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 An adsorption filter was produced in the same manner as in Comparative Example 2, except that 1,2-dichloromethane (1.0 μm / g, average pore size 17 Å) was used. The production conditions and measurement results are shown in Table 3.
[0074] <Comparative Example 4> The downstream layer was a thermal bond nonwoven fabric, and the adsorbent A was granular activated carbon (average particle length 600 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm3 / g, average pore size 17 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17Å) was mixed with thermoplastic powder resin as adhesive in a weight ratio of 7:1:0.4 to give a basis weight of 200g / m 2 The weight of adsorbent A was W A and the weight W of the adsorbent B B Ratio of W A / W B The value P of was 7. An electret nonwoven fabric was used as the upstream layer and heated to obtain an adsorption filter in which an adsorbent was supported on the nonwoven fabric. For this adsorption filter, the number of adsorbent B adhering to the surface of adsorbent A, the ratio of adsorbent B adhering to the surface of adsorbent A, the toluene removal rate, and the pressure loss were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 3. Also, an SEM photograph taken after peeling off the nonwoven fabric on one side is shown in Figure 3.
[0075] <Comparative Example 5> The weight ratio of adsorbent A to adsorbent B is 200:1, i.e., the weight of adsorbent A is W A and the weight W of the adsorbent B B Ratio of W A / W B An adsorption filter was manufactured in the same manner as in Example 2, except that the value P was changed to 200. The manufacturing conditions and the measurement results are shown in Table 3.
[0076] <Comparative Example 6> The downstream layer is made of thermal bond nonwoven fabric, and the downstream layer is made of granular activated carbon (average particle length 150 μm, specific surface area 1000 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 17Å) was mixed with thermoplastic powder resin as adhesive in a weight ratio of 20:1, and the resulting mixture had a basis weight of 200g / m 2 The adsorption filter was obtained by heating an electret nonwoven fabric as the upstream layer and carrying the adsorbent on the nonwoven fabric. The toluene removal rate and pressure loss of this adsorption filter were measured by the above-mentioned method. The manufacturing conditions and the measurement results are shown in Table 3.
[0077] [Table 3]
[0078] As can be seen from Table 2, the adsorption filters of Examples 2 to 16 had a high toluene removal rate and reduced pressure loss.
[0079] In contrast, as can be seen from Table 3, in Comparative Examples 2 and 3 in which adsorbent B was not used, the toluene removal rate was low. A and the weight W of the adsorbent B B Ratio of W A / W B In Comparative Example 4, in which the ratio of adsorbent B adhering to the surface of adsorbent A was small, the toluene removal rate was high but the pressure loss of the adsorption filter was high. This is thought to be because the ratio of adsorbent B that was not adhering to adsorbent A and was free was high, so adsorbent B filled the gaps between the fibers of the nonwoven fabric and caused clogging. Although adsorbent B was used, the weight ratio of adsorbent A to adsorbent B was 200:1, i.e., the weight W of adsorbent A was 1.0, and the toluene removal rate was high. A and the weight W of the adsorbent B B Ratio of W A / W B In Comparative Example 5, in which the value P was 200, the toluene removal rate was low due to the small amount of adsorbent B. In Comparative Example 6, in which activated carbon having an average particle major axis of 150 μm, which does not correspond to adsorbent A or B, was used alone, the toluene removal rate was high, but the pressure loss of the adsorption filter was high.
[0080] Fig. 4 shows a graph illustrating the relationship between the toluene removal rate and pressure loss for the adsorption filters of Examples 1 to 16 and Comparative Examples 1 to 6. The horizontal axis is pressure loss (mmaq) and the vertical axis is toluene removal rate (%). Fig. 4 shows that the adsorption filters of Examples 1 to 16 have a high toluene removal rate relative to the pressure loss, while the adsorption filters of Comparative Examples 1 to 6 have a low toluene removal rate relative to the pressure loss.
[0081] As described above, the adsorption filter of the present invention has a high toluene removal rate and is capable of reducing pressure loss.
[0082] <Example 17> Adsorbent A was silica gel (average particle length 600 μm, specific surface area 600 m 2 / g, pore volume 0.46 cm 3 / g, average pore size 24 Å) and powdered activated carbon (average particle length 15 μm, specific surface area 1000 m) as adsorbent B. 2 / g, pore volume 0.46 cm 3 / g, average pore size 17 Å) were mixed in a weight ratio of 7:1, and an aqueous solution of sodium alginate (ALG-Na) was added in an amount of 0.46 times the total weight of the silica gel and powdered activated carbon and mixed. The molecular weight of sodium alginate (ALG-Na) was 55,000, and the concentration of the aqueous solution of sodium alginate (ALG-Na) was 4.4% by weight. This was dried to obtain an adsorbent in which powdered activated carbon was fixed to the surface of the silica gel. An adsorption filter was also produced using the obtained adsorbent in the same manner as in Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 4.
[0083] <Comparative Example 7> Instead of granular activated carbon, silica gel (average particle diameter 600 μm, specific surface area 600 m 2 / g, pore volume 0.46 cm 3 Except for using an adsorbent of 1000 g / g and an average pore size of 24 Å, an adsorption filter was obtained in the same manner as in Comparative Example 2. The manufacturing conditions and measurement results of the adsorbent are shown in Table 4.
[0084] [Table 4]
[0085] FIG. 5 is a graph showing the relationship between the toluene removal rate and pressure loss when the adsorption filter is made using the adsorbent of Example 17, which uses silica gel as the adsorbent A, and the adsorbent of Comparative Example 7. The horizontal axis is pressure loss (mmaq), and the vertical axis is toluene removal rate (%). From Table 4 and FIG. 5, it can be seen that the filter using the adsorbent of Example 17 has a high toluene removal rate relative to the pressure loss, and the filter using the adsorbent of Comparative Example 7 has a low toluene removal rate relative to the pressure loss. From this, it can be seen that the effect of the present invention can be achieved by adsorbent B being fixed to the surface of adsorbent A, regardless of the type of adsorbent. [Industrial Applicability]
[0086] The method for manufacturing an adsorption filter of the present invention makes it possible to manufacture an adsorption filter capable of efficiently removing contaminants including volatile organic compounds such as toluene and aldehydes with low pressure loss, which is expected to make a great contribution to the industrial world.
Claims
1. A step of preparing an adsorbent A having an average particle length of 200 μm to 1000 μm, an adsorbent B having an average particle length of 0.1 μm to 100 μm, and a substrate; A step of adhering the adsorbent B to a surface of the adsorbent A to obtain an adsorbent; and supporting the adsorbent on the substrate, The weight W of the adsorbent A A and the weight W of the adsorbent B B Ratio of W A / W B The value P is equal to or greater than 0.3 and equal to or less than 150, A method for manufacturing an adsorption filter in which, when the total amount of the adsorbent B is taken as 100%, 65% or more of the adsorbent B is fixed to the surface of the adsorbent A.
2. The average particle length R of the adsorbent A A and the average particle major axis R of the adsorbent B B Ratio of R B / R A The method for manufacturing an adsorption filter according to claim 1, wherein the ratio of the number of particles to the number of particles is 1 / 5000 to 1 / 5.
3. The average particle length R of the adsorbent A A , the average particle major axis R of the adsorbent B B , and the weight ratio P of the adsorbent A to the adsorbent B ((the weight W of the adsorbent A) A ) / (weight W of adsorbent B B )) is P=R A 3 / [{(R A +2R B ) 3 -R A 3 3. The method for producing an adsorption filter according to claim 1, wherein the relationship: x x is 0.1 or more and 10 or less.
4. 3. The method for manufacturing an adsorption filter according to claim 1, wherein the step of obtaining an adsorbent by fixing the adsorbent B to the surface of the adsorbent A includes a step of mixing the adsorbent A, the adsorbent B, and a binder.
5. The method for manufacturing an adsorption filter according to claim 4, wherein the binder is at least one selected from the group consisting of sodium alginate, polyvinyl alcohol, polyacrylamide, carboxymethyl cellulose, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polystyrene sulfonic acid, polyethylene glycol, polypropylene glycol, polyvinyl acetate, and copolymers thereof.
6. 3. The method for manufacturing an adsorption filter according to claim 1, wherein the adsorbent A is any one of activated carbon, activated alumina, silica gel, and zeolite.
7. 3. The method for manufacturing an adsorption filter according to claim 1, wherein the adsorbent B is any one of activated carbon, activated alumina, silica gel, and zeolite.
8. The method for manufacturing an adsorption filter according to claim 1 or 2, wherein the substrate is a nonwoven fabric.
Citation Information
Patent Citations
Filter medium
JP2015157250A
Cohesive activated carbon air filter
JP3612329B2